The occurrence of intrusive growth associated with articulated laticifers in Tabernaemontana catharinensis A.DC., a new record for Apocynaceae - Canaveze, Yve [UNESP]; Machado, Silvia Rodrigues [UNESP] (University of Chicago Press, 2016)
Premise of research. In Apocynaceae, nonarticulated laticifers have been recorded in most species studied. Interpretation of the mode of development of laticifers, whether articulated or nonarticulated, is controversial, possibly because of the rapid changes that occur in the early differentiation stages of the structures. Here, we describe laticifers in the embryo, seedling, and plant of Tabernaemontana catharinensis A.DC. (Apocynaceae), aiming to understand the structure and developmental mechanism of the laticifer system. Methodology. We prepared samples of mature embryos, 20-d-old seedlings, and 80-d-old plants of T. catharinensis according to conventional light microscopy techniques for anatomical and histochemical analysis. Pivotal results. Articulated anastomosing laticifers with intrusive growth, producing proteins, lipids, and terpenes, are present from mature embryos. Alkaloids are present in the laticifer protoplast of the older portions of the stem. Laticifers of the primary system originate from the ground meristem and procambium, and those of the secondary system originate from the vascular cambium toward the secondary phloem. In the embryo, laticifers are found in the ground meristem and procambium but do not occur in the promeristem; the nodal region exhibits lateral projections between laticifers and ground meristem cells. In seedlings and plants, laticifers are immersed in the parenchyma tissue and associated with the primary and secondary phloem of the root and shoot systems. The anatomical evidence suggests the incorporation of meristematic and parenchyma cells within the laticifer system. Conclusions. The laticifer system of T. catharinensis has a complex structure and developmental mechanism involving protoplast fusion, the addition of cells, and intrusive growth. We recorded, for the first time, the occurrence of intrusive growth associated with articulated anastomosing laticifers in a member of Apocynaceae. Our findings highlight the importance of detailed anatomical analysis to properly classify laticifers and to access their origin and development.
Keywords: Inducing action; Intrusive growth; Laticifers; Ontogeny